Clusterin expression is upregulated following acute head injury and localizes to astrocytes in old head injury. Issue 1 (1st July 2016) - Troakes, Claire; Smyth, Rachel; Noor, Farzana; Maekawa, Satomi; Killick, Richard; King, Andrew; Al‐Sarraj, Safa
Abstract : There is mounting evidence linking traumatic brain injury (TBI) to neurodegeneration. Clusterin (apolipoprotein J or ApoJ) is a complement inhibitor that appears to have a neuroprotective effect in response to tissue damage and has been reported to be upregulated in Alzheimer's disease. Here we investigated the time course and cellular expression pattern of clusterin in human TBI. Tissue from 32 patients with TBI of varying survival times (from under 30 min to 10 months) was examined using immunohistochemistry for clusterin alongside other markers of neurodegeneration and neuroinflammation. TBI cases were compared to ischemic brain damage, Alzheimer's disease and controls. Double immunofluorescence was carried out in order to examine cellular expression. Clusterin was initially expressed in an axonal location less than 30 min following TBI and increased in intensity and the frequency of deposits with increasing survival time up to 24 h, after which it appeared to reduce in intensity but was still evident several weeks after injury. Clusterin was first evident in astrocytes after 45 min, being increasingly seen up to 48 h but remaining intense in TBI cases with long survival times. Our results suggest clusterin plays a role in modulating the inflammatory response of acute and chronic TBI and that it is a useful marker for TBI, particularly in cases with short survival times. Its prominent accumulation in astrocytes, alongside a mounting inflammatory response and activation of microglial cells supports a potential role in the neurodegenerative changes that occur as a result of TBI.